HUBUNGAN LAMA PEMAKAIAN KONTRASEPSI SUNTIK DMPA (DEPO MEDROKSI PROGESTERON ASETAT) DENGAN GANGGUAMENSTRUASI PADA AKSEPTOR KONTRASEPSI SUNTIK DI PUSKESMAS OEPOI, KOTA KUPANG - Marsela Diyanasri; Florentianus Tat; Angela Muryanti Gatum (STIKes CHMK, 2023)
Injectable contraceptive DMPA is used for the purpose of parenteral contraception, has a strong and highly effective progestagen effect. DMPA injection has side effects for its users, especially menstrual disorders. Menstrual disorders in the use of injectable contraception depend on the duration of use. The use of DMPA injectable contraception aims to inhibit the occurrence of pregnancy. The research design used was correlational using cross sectional approach. The sampling technique used as purposive sampling. The population in this research is family planning acceptor at Puskesmas Oepoi, Kota Kupang as many as 96 people, the sample is 77 respondents. Data were collected using questionnaires. The result of the research shows that the relationship between the duration of contraceptive use DMPA with amenorrhea p = 0,000 (p value <0.05), there is relationship between the duration of DMPA injection use with hypermorea p = 0,001 (p value <0.05), there was a relationship between the duration of contraceptive use of DMPA with hipomenorea p = 0,000 (p value <0.05), there was a correlation between duration of DMPA injection use with spotting p = 0,001 (p value <0,05). Based on this research it can be concluded that there is a relationship between the duration of contraceptive use DMPA with menstrual disorders. Menstrual disorders are one of the causes of contraceptive acceptor discontent, therefore health workers need to provide information that menstrual disorders are common in the use of injectable contraceptives. Keywords: Old Contraceptive Use, DMPA Injectable Contraception, Menstrual Disorder